2023
DOI: 10.1021/acs.jmedchem.3c00586
|View full text |Cite
|
Sign up to set email alerts
|

Ir(III) Compounds Containing a Terdentate Ligand Are Potent Inhibitors of Proliferation and Effective Antimetastatic Agents in Aggressive Triple-Negative Breast Cancer Cells

Abstract: Herein, we report a series of new octahedral iridium(III) complexes Ir1−Ir9 of the type [Ir(N^N^N)(C^N)Cl]PF 6 (N^N^N = 4′-(p-tolyl)-2,2′:6′,2″-terpyridine; C^N = deprotonated 2-arylbenzimidazole backbone) to introduce new metal-based compounds for effective inhibition of metastatic processes in triple-negative breast cancer (TNBC).The results show that the structural modifications within the C^N scaffold strongly impact the antimetastatic properties of these complexes in TNBC cells. Furthermore, testing the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…53−57 The 1 IL fluorescent emission observed at 362 nm in ACN for complexes Ru1 and Ru2 was more intense than that observed for complex Ru3. All the complexes present weak yellow phosphorescence from 3 MLCT states at room temperature in ACN solutions, see Table 3. The emission from 3 MLCT varies little from one compound to another, which could be indicate of the π* acceptor orbital of 3 MLCT is similar in each complex.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…53−57 The 1 IL fluorescent emission observed at 362 nm in ACN for complexes Ru1 and Ru2 was more intense than that observed for complex Ru3. All the complexes present weak yellow phosphorescence from 3 MLCT states at room temperature in ACN solutions, see Table 3. The emission from 3 MLCT varies little from one compound to another, which could be indicate of the π* acceptor orbital of 3 MLCT is similar in each complex.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…In all complexes, the T 1 state mainly originates from HOMO → LUMO (70%) transition (Table S6) and characterized as 3 MLCT. The other high energy emission band are derived from triplet states which are predominantly ligand centered 3 LLCT/ 3 ILCT. Finally, it is interesting to note that the S 0 −T 1 transition is accompanied by a change in the dipole moment (Table S8), which is greater for Ru5 and Ru1, in particular in water and Ru4 exhibited the lowest change in the dipolar moment in the S 0 −T 1 transition.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the mechanisms of action of Re(I) anticancer complexes containing the fac -[Re(CO) 3 ] + core are quite distinct from that of conventional platinum agents, , that is dependent on covalent bond formation to DNA . Targeting vulnerable organelles, such as the mitochondria, is one strategy that has been employed to combat resistance to chemotherapeutics, and that generally is the case for rhenium(I) tricarbonyl complexes. , However, their in vivo antitumor efficacy is still little known. , Our previous results on ruthenium(II) and iridium(III) organometallic complexes of the types [Ru(C^N)(N^N) 2 ] + , [Ir(C^N) 2 (N^N)] + , and [Ir(C^N)(N^N^N)] + demonstrated that slight modifications on the benzimidazole-based ligand core rendered high anticancer activities in vitro , the N-substituted butyl group serving to adjust the lipophilic properties and enhance cellular uptake and targeting preferentially mitochondria, , whereas the ester group attached to the benzimidazole backbone could act as a handle for further functionalization …”
Section: Introductionmentioning
confidence: 99%